The tip of the iceberg? Reply to responses. (6th August 2015) - Anderson-Whymark, Hugo; Garrow, Duncan; Sturt, Fraser
<x content-type="archive" xml:space="preserve">Abstract</x> We would like to thank all four authors for their thoughtful responses to our paper and the assemblage it describes. In some cases those comments confirmed things we had thought already, but in others they surprised us, confronting us with ideas that we had never previously considered. Collectively this has made us think hard about future research possibilities.